The Subject of Retirement - Cameron Graham (Foucault Studies, 2012)
This paper examines the ”subject of retirement,” one of the most intimate governmental technologies of our present. It extends Read’s argument regarding Foucault’s views on neoliberalism, by providing explicit examples of the technologies of neoliberal government. Read drew attention to the intensification of governmentality by which neoliberalism has operated, and its pervasion into every aspect of society as the individual-as-citizen is transformed into the individual-as-entrepreneur. By examining the Canadian retirement income system, this paper provides a specific example of accounting as a tool of governmentality, a technology integral to neoliberalism’s regime of truth and its production of subjectivity.